The Effect of STEM-Based Differentiated Learning to Improve Students' Critical Thinking Skills: A Meta-Analysis Study - Haetami Haetami (Postgraduate, University of Mataram, 2023)
This study aims to determine the effect of differentiated learning to improve students' critical thinking skills. The type of research is meta-analysis. The samples of this study came from 13 national and international journals. The process of searching for research samples through Google Scholar, ScienceDirect, Eric, Springer, Plos ONE, MPDI, and ProQuest databases. The inclusion criteria were Research must be national and international journals indexed by SINTA, WOS, and Scopus; Research must be experimental or quasi-experimental; Research from national and international journals published in 2019-2023; 4) Research has a relationship with research variables; 5) Research data must have t, f, and standard deviation values. The data selection process is the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) method. Data analysis is statistical analysis with the help of JSAP. The results concluded that the average effect size value of the whole study was 0.892 with high criteria. This finding shows that STEM-based differentiated learning has a significant effect on students' critical thinking skills.